Facial and occlusal esthetic improvements of an adult skeletal class iii malocclusion using surgical, orthodontic, and implant treatment - Cardoso, Mauricio de Almeida; de Molon, Rafael Scaf [UNESP]; De Avila, Erica Dorigatti [UNESP]; Guedes, Fabio Pinto; Filho, Valter Antonio Ban Battilani; Filho, Leopoldino Capelozza; Correa, Marcio Aurelio; Filho, Hugo Nary (Korean Association of Orthodontists, 2016)
The aim of this clinical report is to describe the complex treatment of an adult Class III malocclusion patient who was disappointed with the outcome of a previous oral rehabilitation. Interdisciplinary treatment planning was performed with a primary indication for implant removal because of marginal bone loss and gingival recession, followed by orthodontic and surgical procedures to correct the esthetics and skeletal malocclusion. The comprehensive treatment approach included: (1) implant removal in the area of the central incisors; (2) combined orthodontic decompensation with mesial displacement and forced extrusion of the lateral incisors; (3) extraction of the lateral incisors and placement of new implants corresponding to the central incisors, which received provisional crowns; (4) orthognathic surgery for maxillary advancement to improve occlusal and facial relationships; and finally, (5) orthodontic refinement followed by definitive prosthetic rehabilitation of the maxillary central incisors and reshaping of the adjacent teeth. At the three-year follow-up, clinical and radiographic examinations showed successful replacement of the central incisors and improved skeletal and esthetic appearances. Moreover, a Class II molar relationship was obtained with an ideal overbite, overjet, and intercuspation. In conclusion, we report the successful esthetic anterior rehabilitation of a complex case in which interdisciplinary treatment planning improved facial harmony, provided gingival architecture with sufficient width and thickness, and improved smile esthetics, resulting in enhanced patient comfort and satisfaction. This clinical case report might be useful to improve facial esthetics and occlusion in patients with dentoalveolar and skeletal defects.
Keywords: Dental implants; Esthetics; Orthodontics; Orthognathic surgery